Factors influencing sickness at Central Bull Test Station - O'Banion, D.S.; Zoellner, K.O.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station, 2011)
Pre-test management was studied on 351 bulls from 54 herds that were tested at the Kansas Bull Test Station at Beloit, Kansas. Charolais, Hereford, Polled Hereford, and Simmental bulls were sick more days than Angus or Limousin between delivery and start of test. Starting ages and weight correlated significantly with sickness. Bulls sick the least had been vaccinated with BVD, IBR, PI3, Pasturella, Blackleg, malignant edema, and lepto before arriving for test.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Sickness; Age; Weight